1995
DOI: 10.1212/wnl.45.12.2233
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative hippocampal MRI and intractable temporal lobe epilepsy

Abstract: Quantitative MRI combining HCT2 and HCVR is a reliable method for diagnosing hippocampal sclerosis noninvasively. End-folium sclerosis and amygdala sclerosis should be considered in patients with intractable TLE and negative findings on MRI studies, including quantitative measures of the hippocampus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(91 citation statements)
references
References 11 publications
5
83
1
2
Order By: Relevance
“…Jackson et al originally reported that T2 relaxometry maps were abnormal in all patients with MTS (18). However other groups have reported relatively lesser sensitivity (19), in our study the sensitivity of T2 relaxometry to identify the affected side is only 85 % similar to other study. Majority of the patients who had loss of volume also had longer T2 relaxation.…”
Section: Discussionsupporting
confidence: 77%
“…Jackson et al originally reported that T2 relaxometry maps were abnormal in all patients with MTS (18). However other groups have reported relatively lesser sensitivity (19), in our study the sensitivity of T2 relaxometry to identify the affected side is only 85 % similar to other study. Majority of the patients who had loss of volume also had longer T2 relaxation.…”
Section: Discussionsupporting
confidence: 77%
“…17,18 The anatomy of the hippocampus is quite intricate, with curved surfaces and layers of gray and white matter that render parcellation of the cortex from subcortical content a difficult task. The plane of orientation also does not lend itself to easy assessment in the axial plane: This is the plane in which neuroradiologists are often most comfortable.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have demonstrated considerable efficacy, especially with the addition of T2 relaxation time data. [36][37][38][39][40][41] Patients with mesial temporal lobe epilepsy exhibit smaller hippocampal volumes. 16,[42][43][44][45][46][47] This hippocampal volume reduction is highly concordant with the side of the epileptogenic focus, and hippocampal deficits are most pronounced ipsilateral to the epileptic focus.…”
Section: Temporal Lobe Epilepsymentioning
confidence: 99%